2021
DOI: 10.3390/min11050502
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks and Source Analysis of Heavy Metal Pollution from Dust in Tianshui, China

Abstract: The purpose of this study is to explore the degree and spatial distribution of dust heavy metal pollution in Tianshui City, the health risks, and the sources of heavy metals. The geoaccumulation index and health risk assessment are used to study pollution levels and human health risks, and Cu, Zn, and Pb pollution are found to be serious. The total exposure of children to dust and heavy metals is 8.329 × 10−3 mg·kg−1·d−1, which is 4.66 times that of adults. The effect of carcinogenic heavy metal exposure is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Another study in Maha Sarakham Municipality, Thailand, reported road dust to be uncontaminated to moderately contaminated by Cu [ 17 ]. In Tianshui, China, Tan et al [ 50 ] witnessed road dust to be uncontaminated to moderately contaminated by Cu and As, while in Dhaka city, Bangladesh, Rahman et al [ 45 ] discovered road dust to be uncontaminated to moderately contaminated by Rb.…”
Section: Resultsmentioning
confidence: 99%
“…Another study in Maha Sarakham Municipality, Thailand, reported road dust to be uncontaminated to moderately contaminated by Cu [ 17 ]. In Tianshui, China, Tan et al [ 50 ] witnessed road dust to be uncontaminated to moderately contaminated by Cu and As, while in Dhaka city, Bangladesh, Rahman et al [ 45 ] discovered road dust to be uncontaminated to moderately contaminated by Rb.…”
Section: Resultsmentioning
confidence: 99%
“…One commonly used rate is the Geoaccumulation Index (I geo ). Other indicators proposed in this study include the Contamination Factor (CF) and the Pollution Load Index (PLI) [1,2,42,56,57] (Table 2). A geochemical index, proposed by Müller [58], is used to determine the degree of soil contamination:…”
Section: Assessment Of Roadside Soil Contaminationmentioning
confidence: 99%
“…The development of civilization has contributed to severe environmental pollution [1][2][3]. In addition to industry and agriculture, road transport is a primary source of trace element pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes in soil composition are peculiarly important in the case of crops for which a sufficient supply of essential elements has to be ensured, whilst potentially toxic elements should be present only at very low levels. Since heavy metals are now ranked in second place when taking into account the degree of risk they pose to the human population all over the world, in recent years there has been increasing concern about environmental contamination from them [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it leads to limiting the productivity of agricultural crops [ 20 ]. The danger of metallic elements lies also in the fact that many of them are dispersed in the environment for a long time and, therefore, they are considered to be persistent [ 12 ]. As an example, half-life time varies from 75 to 380 years for cadmium (Cd) and from 1000 to 3000 years for copper (Cu), nickel (Ni), lead (Pb), zinc (Zn), and selenium (Se) in the soils of temperate climates [ 21 ].…”
Section: Introductionmentioning
confidence: 99%